The gloom and doom surrounding energy poverty - Al-Herbish, S (Oxford Institute for Energy Studies, 2010)
Energy security is always high on the agenda of both consumers and producers but rarely does the international debate focus on those hundreds of millions of people without any access to modern energy. Authoritative studies suggest that, even in 2030, there will be 1.3 billion people without electricity: this figure is only 200 million below today’s estimate, meaning that increased power generation capacity worldwide is expected only to nearly offset the additional needs created by an increasing population. Despite the genuine gains in development in many parts of the world, ‘business as usual’ policies will merely condemn many of the poorest to life without clean and efficient energy services. Such services are essential to advance human development and provide opportunities for economic and social progress. We, the OPEC Fund for International Development (OFID), certainly believe that the international community can do better than this.